DENTIFICATION OF ENVIRONMNTALLY FISHING GEARS OPERATING IN SINGKARAK LAKE OF SUMATERA BARATPROVINCE - Anggun Anggraini; Pareng Rengi; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The study was conducted in July – August 2018  in Singkarak Lake of Sumatera Barat  Province. This study aims to(1) identifiy the environmentally friendly fishing gearsin accordance with the FAO (1995),(2) know the fishing gear that has highest level of environmental friendliness. The method used is the survey method is with direct observation in the field and conducting interview with fishermen, Collecting data using a questionnaire and analyzed using descriptive analysis of the results of the research described in graphic form, and tables. Based on field observations in the know that fishing gear used by fishermen in lake Singkarak is classified as a very enviromental friendly and eviromental friendly fishing gear and not eviromental friendlyfishing gear. The results of this research showed that fishing rod, gillnet, cast netare a very enviromental friendly fishing gear, while lift net are an enviromental friendly fishing gear and fish trap not are an enviromental friendly fishing gear. Keywords :Identification,CCRF,Fishing gears, FAO, environmentally friendly